Evaluating Goals in Worker Health Protection Using a Participatory Design and an Evaluation Checklist. (February 2014) - Ahonen, Emily Q.; Zanoni, Joseph; Forst, Linda; Ochsner, Michele; Kimmel, Louis; Martino, Carmen; Ringholm, Elisa; Rodríguez, Eric; Kader, Adam; Sokas, Rosemary
Spanish-speaking immigrant workers in construction are considered hard to reach and at high risk for work-related injury and fatality. This evaluation study describes the use of participatory methods and an evaluation checklist to consider a health and safety (H&S) training program for these workers. A previously developed training manual and model were disseminated to eight worker centers (WCs) through participatory research collaboration. It incorporated H&S training for workers while strengthening the role of WCs as sources for leadership development and worker empowerment. Design, delivery, reaction, application, and extension were assessed through individual interviews with participants, trained trainers, and center staff and through observation of training sessions and partner debriefs; pre- and post-training tests assessed participant learning. Results indicate moderate learning and application by participants and strong evidence for structural gains in and among WCs. We conclude that such partnerships and models are valuable tools for collaborating with hard-to-reach workers.